Disparities in access to COVID-19 vaccine in Verona, Italy: a cohort study using local health immunization data - Benoni, Roberto; Sartorello, Anna; Moretti, Francesca; Marchiori, Francesco; Accordini, Luciana; Postiglione, Chiara; Coffele, Viviana; Tardivo, Stefano (Frontiers in Public Health, 2023)
The migrant population has been disproportionately affected by the COVID-19 pandemic. Although COVID-19 vaccination campaigns have committed substantial resources worldwide, migrants have shown lower vaccine coverage and uptake. This study aims to explore the country of birth as a factor influencing access to COVID-19 vaccine. The retrospective cohort study included adults vaccinated against SARS-CoV-2 with at least one dose in the Verona administration between 27/12/2020 and 31/12/2021. Time-to-vaccination was estimated as the difference between the actual date of each person's first dose of COVID-19 vaccination and the date on which the Local Heath Authorities opened vaccination reservations for the corresponding age group. The birth country was classified based on both the WHO regions and the World Bank country-level economic classification. Results were reported as Average Marginal Effect (AME) with a 0.95 confidence interval. During the study period, 754,004 first doses were administered and 506,734 (F=246,399-48.6%) were included after applying the exclusion criteria. Foreigners were 85,989 (17.0%, F=40,277–46.8%), with a mean age of 42.4 years (SD 13.3). The mean time-to-vaccination in the whole sample was 46.9 days (SD 45.9), 41.8 days (SD 43.5) in the Italian population, and 71.6 days (SD 49.1) in the foreign group (p<0.001). The AME of the time-to-vaccination compared to the Italian population was higher by 27.6 [0.95CI 25.4-29.8], 24.5[0.95CI 24.0-24.9], 30.5[0.95CI 30.1-31.0] and 7.3 [0.95CI 6.2-8.3] days in LIC, LMIC, UMIC, and HIC, respectively. Considering the WHO area, the AME of the time-to-vaccination compared to the Italian group was higher by 31.5 [0.95CI 30.6-32.5], 31.1[0.95CI 30.6-31.5], and 29.2[0.95CI 28.5-29.9] days in AFR, EUR, and EMR. Time-to-vaccination decreased with increasing age (p<0.001). Apart from Hub centre, the most used by both populations, pharmacies, and local health units were used more by foreigners (2.9%, 1.5%), while EUR and Italians relied more on family doctors (4.2% and 3.3%). The birth country proved to be a factor influencing the COVID-19 vaccine access both in terms of time and vaccination point used. The elderly showed higher vaccination-seeking behavior with a lower time-to-vaccination. Public Health stakeholders should consider socio-cultural and economic barriers to healthcare access when planning massive vaccination campaign interventions.